Pelvic Rocking Exercise Terhadap Penurunan Intensitas Nyeri Dismenore Pada Remaja Putri - Ammiruddin, Sri Hennyati; Sagita, Via Mira (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2024)
The loss of the inner uterine wall is what causes menstrual bleeding. Pain during the menstrual cycle is often referred to as dysmenorrhea. Hormonal fluctuations during the reproductive cycle can cause dysmenorrhea, or discomfort during the menstrual period. During menstruation, an increase in the hormone prostaglandin causes the muscles of the uterus to tighten, resulting in discomfort. In West Java, dysmenorrhea is quite common (51.86%). Pelvic rocking exercise, a type of pelvic physical exercise designed to strengthen the abdominal muscles and increase blood flow to the uterus, can be used to treat dysmenorrhea. In this study, the effectiveness of pelvic rocking exercise in reducing the severity of dysmenorrhea discomfort in adolescent girls at SMPN 01 Tanjungsari Sumedang was tested. The study employed a quasi-experimental technique using a pretest-posttest design for one group. Forty-five female students who experienced dysmenorrhea were sampled in this study using a total sampling approach. In this study, Wong Baker Paint Rating Scale questionnaire was used as an instrument. Data analysis used Wilcoxon non-parametric statistical test. The findings showed Wilcoxon with a significance level of 0.05 and a p value of 0.000. In this study, the P value is less than 0.05 (0.000 < 0.05), it can be said that there is an effectiveness of pelvic rocking exercise on reducing dysmenorrhea pain intensity.